2015
DOI: 10.1177/1932296814567533
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Glide Force Characteristics Between 2 Prefilled Insulin Lispro Pens

Abstract: Glide force, average glide force, and glide force variability of the insulin lispro 200 units/mL pen (Eli Lilly and Company, Indianapolis, IN, USA) were compared to the Humalog KwikPen 100 units/mL pen (hereafter, KwikPen; Eli Lilly and Company, Indianapolis, IN, USA). Data were collected on 2 doses, 2 injection speeds, and 2 needle types. Insulin lispro 200 units/mL pen showed significantly lower maximum glide force, average glide force, and glide force variability than the KwikPen across all combinations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…A literature search was conducted to support health state content and guide subsequent discussions with clinicians. The literature search focused on standard (100 units/mL) and concentrated (200 units/mL) insulin lispro product information [18], glide force (i.e., the amount of effort required to press the pen's injection button) [31], and patient perceptions of standard and concentrated insulin [32][33][34][35].…”
Section: Health State Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature search was conducted to support health state content and guide subsequent discussions with clinicians. The literature search focused on standard (100 units/mL) and concentrated (200 units/mL) insulin lispro product information [18], glide force (i.e., the amount of effort required to press the pen's injection button) [31], and patient perceptions of standard and concentrated insulin [32][33][34][35].…”
Section: Health State Developmentmentioning
confidence: 99%
“…The first and third of these differences are objective characteristics of the injection pens, as indicated in the Summary of Product Characteristics [18]. The second difference, ''effort to inject'' (i.e., glide force), has been examined in a previously published study, which found that the concentrated insulin pen required less effort (i.e., lower glide force) than the standard insulin pen [31].…”
Section: Health State Developmentmentioning
confidence: 99%
“…20 Recently developed concentrated insulins include insulin degludec (200 unit/mL formulation; Novo Nordisk, Bagsvaerd, Denmark), 21 insulin glargine (300 unit/ mL formulation; sanofi-aventis US LLC, Bridgewater, NJ, USA), 22 and insulin lispro (200 unit/mL; Eli Lilly and Company, Indianapolis, IN, USA). 23 The prefilled insulin delivery devices that contain these concentrated insulins dial and dose in actual units such that no conversion is needed based on the concentration. [21][22][23] The Humalog® 200 units/mL KwikPenTM.…”
mentioning
confidence: 99%
“…23 The prefilled insulin delivery devices that contain these concentrated insulins dial and dose in actual units such that no conversion is needed based on the concentration. [21][22][23] The Humalog® 200 units/mL KwikPenTM. (insulin lispro 200 units/mL, hereafter, IL 200 pen; Eli Lilly and Company, Indianapolis, IN, USA) insulin delivery device was recently approved in the US 24 and in the European Union.…”
mentioning
confidence: 99%
See 1 more Smart Citation